A novel AgNP/DNA/TPdye conjugate-based two-photon nanoprobe for GSH imaging in cell apoptosis of cancer tissue. Issue 94 (5th October 2015) - Tang, Qiao; Wang, Ningning; Zhou, Fulin; Deng, Ting; Zhang, Songbai; Li, Jishan; Yang, Ronghua; Zhong, Wenwan; Tan, Weihong
Abstract : By combining DNA with a two-photon dye (TPdye) and silver nanoparticles (AgNPs), a novel two-photon nanoprobe for glutathione (GSH) imaging in cell apoptosis of cancer tissue was designed in the present study. Abstract : In the present study, a novel two-photon nanoprobe has been developed and successfully applied in glutathione (GSH) imaging in cell apoptosis of cancer tissue.